The Role of Subordinated Debt in Market Discipline : The Case of Emerging Markets - Karacadag, Cem (IMF Working Papers; Working Paper ;, 2000)
This paper evaluates the potential role of mandatory subordinated debt (MSD) in enhancing market discipline in emerging markets. The conceptual merits and key preconditions of MSD are first reviewed. Then, the extent to which emerging markets satisfy these preconditions-among them the monitorability of bank assets, the presence of nonbank financial investors, and liquid and 'clean' capital markets-are evaluated. We find that emerging markets do not satisfy the preconditions for the successful implementation of a MSD policy. Therefore, efforts to enhance market discipline should first focus on satisfying these preconditions and improving the overall incentive environment and market infrastructure.